The role of bystander-initiated basic life support in exercise-related sudden cardiac arrest: a systematic review. (14th October 2021) - Grubic, N; Hill, B; Phelan, D; Baggish, A; Dorian, P; Johri, A.M
Abstract: Background: Sudden cardiac arrest (SCA) is the leading cause of death amongst athletes and a common cause of death during exercise. Although the provision of cardiopulmonary resuscitation (CPR) and automated external defibrillator (AED) use by bystanders improves outcomes after SCA, the impact of these interventions within exertional settings requires further investigation. Purpose: The purpose of this systematic review was to evaluate the role of bystander CPR and AED use on survival after exercise-related SCA. Methods: Literature searches in MEDLINE, EMBASE, PubMed, CINAHL, SPORTDiscus, and Cochrane Library were queried from inception until November 2020 using a comprehensive search strategy. Grey literature searches of Google Scholar and CADTH Grey Matters were also performed. Abstract screening, full-text review, and data extraction of eligible studies was conducted independently by two reviewers, with any conflicts discussed until consensus reached. Eligible studies included observational research studies assessing a population of exercise-related SCAs (defined as an out-of-hospital cardiac arrest which occurred during exercise or within 1-hour of cessation of activity), where the rate of bystander CPR and/or AED use was provided, and survival outcomes were reported. Abstracts, studies with overlapping patient data, and/or studies of n≤10 were excluded. Among studies with similar populations, the overall rates (median, range) of bystander CPR, AED use, and survival outcomes were calculated. Results: A total of 3, 718 records were identified from literature searches, and after removal of duplicates, 2, 850 were screened. Among those screened, 176 articles were selected for full-text review, of which 29 studies were included in this review. Majority of included studies were cohort studies (2 case series and 2 cross-sectional), with a median sample size of 91. Most patients who suffered from an exercise-related SCA were male, middle-aged, and presented with a shockable arrest rhythm. The median rate of bystander CPR reported amongst 22 studies was 71% (31%-100%), whereas the median rate of bystander AED use reported amongst 16 studies was 31% (2%-100%) (Table). Among the 19 studies which reported the rate of survival to hospital discharge, survival ranged from 11% to 77%, with a median rate of 32% (Table). Patients who survived to hospital discharge more frequently received bystander CPR and had an AED applied than patients who died (Figure). Conclusions: Survival rates after exercise-related SCA were higher than previously reported in other settings not related to exercise. These outcomes are likely related to a higher rate of bystander interventions in exertional or sport-specific settings. The findings of this review encourage layperson education in basic life support, the availability of AEDs in exercise facilities, and the development of emergency action plans to provide point-of-performance cardiac care in exertional settings. Funding Acknowledgement: Type of funding sources: None.